KEWENANGAN PEMERINTAH TERHADAP ORGANISASI OLAHRAGA PSSI - Suparman, Yusup (Universitas Wiralodra, 2021)
The existence of the PSSI organization in Indonesia has its own uniqueness. This uniqueness can be seen from their status as members of FIFA in the international world and as a sports organization that has the status as a legal entity in the country of Indonesia whose existence is a member of the Indonesian National Sports Committee (KONI). In the concept of this scientific paper using the normative juridical research method. As well as using data collection techniques carried out using descriptive analysis techniques, with secondary data sources, which include primary legal materials such as laws and regulations relating to the statute and position of PSSI both in Koni membership and in FIFA membership. The PSSI statutes also explain the existence of PSSI as a member of FIFA, so the existence of the PSSI statute explains that the existence of PSSI in Indonesia is an independent organization and its existence as a member of FIFA, so that the regulations established by PSSI are based on rules made by FIFA. In Indonesia, PSSI is a sports organization, this existence is based on the provisions in Article 35 paragraph (1) of the Act No. 3 of 2005 concerning the National Sports System, namely